Molecular requirements of the B‐cell antigen receptor for sensing monovalent antigens. (15th September 2016) - Volkmann, Christoph; Brings, Naema; Becker, Martin; Hobeika, Elias; Yang, Jianying; Reth, Michael
Abstract: How the B‐cell antigen receptor (BCR) is activated upon interaction with its cognate antigen or with anti‐BCR antibodies is not fully understood. We have recently shown that B‐cell activation is accompanied by the opening of the pre‐organized BCR oligomers, an observation that strengthens the role of receptor reorganization in signalling. We have now analysed the BCR oligomer opening and signalling upon treatment with different monovalent stimuli. Our results indicate that monovalent antigens are able to disturb and open the BCR oligomer, but that this requires the presence and activity of the Src family kinase (SFK) Lyn. We have also shown that monovalent Fab fragments of anti‐BCR antibodies can open the BCR oligomers as long as they directly interact with the antigen‐binding site. We found that monovalent antigen binding opens both the IgM‐BCR and IgD‐BCR, but calcium signalling is only seen in cells expressing IgM‐BCR; this provides a molecular basis for IgM‐ and IgD‐BCR functional segregation. Synopsis: B‐cell receptors (BCRs) form oligomers on resting B cells, inconsistent with the cross‐linking model that suggests antigen‐mediated B‐cell receptor dimerization as initiating intracellular signal transduction. Work with monovalent antigens shows how they can trigger signalling despite being unable to induce cross‐linking of receptor monomers. Fab‐based proximity ligation assays directly monitor antigen‐induced BCR conformation changes at 10–20 nm distances. Monovalent antigens can disturb and open the BCR oligomer, dependent on the presence of the Src family kinase Lyn. Monovalent Fab fragments from anti‐idiotypic antibodies also open the BCR oligomer, as long as they directly bind to the antigen‐binding site of the BCR. Monovalent antigens open both IgM‐BCR and IgD‐BCR, but calcium signalling is only triggered in cells expressing IgM‐BCR. Abstract : Proximity ligation assays reveal that monovalent antigen‐binding site ligands are sufficient to induce B‐cell receptor conformational changes, promoting downstream intracellular signalling.